Interfirm Relationships in Emerging Markets: The Importance of Relationships and Cultural Sensitivity. Issue 2 (3rd April 2017) - Voldnes, Gøril; Kvalvik, Ingrid
ABSTRACT: While interfirm relationship value has attracted considerable attention in a domestic market context, little research has examined international buyer-seller relationships. This is surprising, as interfirm relationships across national borders have become increasingly important due to growing liberalization of world trade. Even less research is found including emerging markets. This study use cases with Norwegian seafood export to Turkey as illustrations of the importance of relationship value and cultural sensitivity when conducting business with an emerging country such as Turkey. The data is based on in-depth interviews of Turkish importers.